1998
DOI: 10.1016/s0896-6273(00)80989-7
|View full text |Cite
|
Sign up to set email alerts
|

The bHLH Protein NEUROGENIN 2 Is a Determination Factor for Epibranchial Placode–Derived Sensory Neurons

Abstract: neurogenin2 encodes a neural-specific basic helix-loop-helix (bHLH) transcription factor related to the Drosophila proneural factor atonal. We show here that the murine ngn2 gene is essential for development of the epibranchial placode-derived cranial sensory ganglia. An ngn2 null mutation blocks the delamination of neuronal precursors from the placodes, the first morphological sign of differentiation in these lineages. Mutant placodal cells fail to express downstream bHLH differentiation factors and the Notch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
408
1
4

Year Published

1999
1999
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 422 publications
(428 citation statements)
references
References 44 publications
15
408
1
4
Order By: Relevance
“…This observation indicates that a regulatory mechanism for ngn-2 expression differs from that for ngn-1 expression. It has been reported that ngn-2 is a specification factor for distal placode-derived sensory neurons in epibranchial ganglia (Fode et al, 1998). In the same ganglia, ngn-1 is essential for the specification of proximal neural crest-derived sensory neurons (Ma et al, 1998).…”
Section: Effects Of Signaling Molecules On the Expression Of Neurogeninsmentioning
confidence: 99%
“…This observation indicates that a regulatory mechanism for ngn-2 expression differs from that for ngn-1 expression. It has been reported that ngn-2 is a specification factor for distal placode-derived sensory neurons in epibranchial ganglia (Fode et al, 1998). In the same ganglia, ngn-1 is essential for the specification of proximal neural crest-derived sensory neurons (Ma et al, 1998).…”
Section: Effects Of Signaling Molecules On the Expression Of Neurogeninsmentioning
confidence: 99%
“…For example, members of the basic helixloop-helix transcription factor family, neurogenin1 (ngn1) and neurogenin2 (ngn2) are expressed in different subsets of ganglia dependent on species, and functional analyses showed that ngn genes are important for the development of the epibranchial ganglia (Fode et al, 1998;Ma et al, 1998;Schlosser and Northcutt, 2000;AbuElmagd et al, 2001;Andermann et al, 2002). Indeed, ectopic expression of ngn1 induces formation of excessive neurons in Xenopus and zebrafish embryos (Ma et al, 1996;Blader et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, ectopic expression of ngn1 induces formation of excessive neurons in Xenopus and zebrafish embryos (Ma et al, 1996;Blader et al, 1997). Gene targeting in mice showed that Ngn2 is required for delamination, migration, and differentiation of neurons in the facial and glossopharyngeal placodes (Fode et al, 1998), and morpholino knockdown of ngn1 in zebrafish blocked differentiation of all cranial ganglia (Andermann et al, 2002). Furthermore, many studies have shown that sox2 and sox3, members of the Sox gene family, are expressed in the epibranchial placodes at the earliest stage of placode development in chicks Ishii et al, 2001), frogs (Mizuseki et al, 1998), medaka (Koster et al, 2000), and zebrafish (Okuda et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Transcription factors neurogenin, foxd3 and NeuroD (Fode et al, 1998;Ma et al, 1998;Kim et al, 2001;Andermann et al, 2002), chemokine guidance receptor Cxcr4b (Knaut et al, 2005;Haas and Gilmour, 2006), and cell adhesion molecule cadherin-2 (Kerstetter et al, 2004) have been implicated in the development of the cranial ganglia and/or lateral line system.…”
Section: Introductionmentioning
confidence: 99%